Unusual metastasis of clear cell renal cell carcinoma (Revista Argentina de Cirugía, 2021)
The falciform ligament is a peritoneal reflection that attaches the liver to the anterior abdominal wall; its lower edge contains the round ligament (RL). Single lesions in the RL are rare and usually correspond to perivascular epithelioid cell tumors. We present a case report of a single metastasis in the RL in a patient with clear cell renal cell carcinoma who underwent surgery five years ago. We conducted a literature review to identify similar cases and we found two case reports of single metastasis in the RL.Our patient was a 71-year-old man with a history of renal cell carcinoma who underwent left laparoscopic radical nephrectomy (stage pT3a), laparoscopic right adrenalectomy and total thyroidectomy due to multinodular goiter. The pathological examination revealed metastases of renal cell carcinoma.A computed tomography (CT) scan performed at 5-year follow-up showed a focal lesion in segment IVa with no FDG uptake in the PET scan, but as malignancy was suspected, the patient underwent exploratory laparatomy with no evidence of peritoneal implants. A 1-cm node was found in the round ligament that was completely resected. The pathological examination revealed metastatic clear cell renal cell carcinoma. The RL is involved in cases of peritoneal carcinomatosis and only two cases of single metastasis have been reported: in one patient with papillary renal cell carcinoma pT1aN0 and another one with left breast adenocarcinoma.
Keywords: metastasis; round ligament; renal cell carcinoma